Endogamous Marriages in Kiai Sukorejo's Family: Sufi Social Fiqh Transformation and Implications for Islamic Jurisprudence - Mirwan, Mirwan; Firmansyah, Mohammad; Al Munawar, Faishal Agil; Kolopita, Abdul Fajri (IAIN Manado, 2023)
Marriage with the principle of endogamy in the context of arranged marriages, as observed within the family of Kiai Sukorejo in Situbondo, is influenced by religious, cultural, and Sufi tradition factors. The research uses the phenomenological method to delve into the meaning behind the phenomenon. Marriage is regarded as a means to follow the Sunnah of the Prophet, strengthen religious devotion and Faith, reinforce family bonds, and preserve the existence of the Islamic boarding school (Boarding School). Aspects of lineage, religious commitment, and scholarly qualifications take precedence in arranged marriages as an implementation of the concept of kafa'ah in Islamic jurisprudence (Fiqh). The mystical understanding derived from Sufi teachings also affects perspectives and actions in accepting arranged marriages. This research provides a significant contribution to understanding social Sufi jurisprudence (Fiqh) and the practice of endogamous marriages within the context of Islamic boarding schools. The study's findings offer valuable recommendations for developing social fiqh understanding, remarkably grounded in Sufi teachings. It is important to note that this study has a limitation in that it did not involve female informants, which should be a crucial consideration in analyzing and exploring the meaning of arranged marriages.